The effect of monitoring and evaluation implementation on the transparency of Parepare City bappeda financial reports - Zulkarnaen, Muh. Faiq; Nurman; Ruma, Zainal (Junal Ilmu Manajemen, 2024)
This research aims to determine the effect of monitoring and evaluation on the transparency of the Parepare City Bappeda financial reports. This research is quantitative research. The data used in this research are primary data and secondary data with a population of 50 people. The method used to analyze the relationship between the independent variable and the dependent variable is descriptive, classical assumption test, validity test, reliability test and simple linear regression analysis. The results of this research show that the monitoring variable has a positive and significant effect on the transparency of the Parepare City Bappeda's financial reports, evaluation also has a significant effect on the transparency of the Parepare City Bappeda's financial reports